(untitled) (LEARNing Landscapes, 2008)
This commentary presents 10 guiding principles on leadership that are rooted in the author’s 35-year career as a teacher and administrator. The author stresses the inevitability of change in education, the complexity of this work, and the need to be responsive to evolving situations. He states that attention to relationships is the most important element of leadership and, ultimately, student success.